Mobility, Scarring and Job Quality in Indonesia’s Labor Market - Naidoo, Darian; Packard, Truman; Auwalin, Ilmiawan (World Bank, Washington, DC, 2015)
This paper investigates the occupational mobility and job quality of young people in Indonesia and relates this to the concept of “scarring.” The concept of labor market scarring in this paper is the occurrence of low or zero returns to certain types of work (for example, self-employment). Scarring is expected to occur whenever an individual spends periods working in occupations in which their human capital is either stagnant or deteriorating. Fixed effects estimations using panel data from the Indonesian Family Life Survey reveal that a period in self-employment is associated with negative returns for youth (about 3 to 4 percent per year penalty), but not for older adults. In addition, there are clear patterns of persistence in self-employment over time with few individuals progressing from petty self-employment to businesses with permanent workers.